Erythrocyte ATP levels in mice infected with Plasmodium berghei malaria - S. Areekul (2018)
Adenosine triphosphate (ATP) content was determined in erythrocytes of normal and P. berghei infected mice by the luciferase enzyme and the liquid scintillation counter. The erythrocyte ATP level in P. berghei infected mice was found to be significantly higher than in normal mice, and there was no relationship between these values and the level of parasitaemia. An inverse relationship between parasitaemia and the ATP content in parasitized red cells was observed while the nonparasitized red cells showed the same content of ATP as in the normal erythrocytes.